2012
DOI: 10.4236/jacen.2012.11002
|View full text |Cite
|
Sign up to set email alerts
|

Residue patterns of buprofezin and teflubenzuron in treated peaches

Abstract: The biological half-life and final residue levels of buprofezin and teflubenzuron were examined in peaches over a 14-day cultivation period. The residue levels of buprofezin and teflubenzuron were analyzed by chromatographic method with recovery ranging from 84.0% to 96.6%. The biological half-lives of buprofezin and teflubenzuron were 4.88 and 11.49 days at the standard dose, and 4.40 and 10.86 days at a triple dose, respectively. The initial concentration of buprofezin exceeded the maximum residue limit (MRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Another factor that influences the dissipation of buprofezin might be the coarse surface of the cauliflower that allows more attraction and persistence of the pesticide. Yoon, Park, Han and Lee () reported the t 1/2 to be 4.88 and 4.4 days in peaches at application rates of 400 and 1200 g a.i. h −1 , respectively (Yoon et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that influences the dissipation of buprofezin might be the coarse surface of the cauliflower that allows more attraction and persistence of the pesticide. Yoon, Park, Han and Lee () reported the t 1/2 to be 4.88 and 4.4 days in peaches at application rates of 400 and 1200 g a.i. h −1 , respectively (Yoon et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Yoon, Park, Han and Lee () reported the t 1/2 to be 4.88 and 4.4 days in peaches at application rates of 400 and 1200 g a.i. h −1 , respectively (Yoon et al, ). Oulkar et al () reported that residues of buprofezin in grapes dissipated following a nonlinear two‐compartment first + first‐order kinetics, with the t 1/2 determined at 3 days at single and double application rates of 312.5 and 625 g a.i.…”
Section: Resultsmentioning
confidence: 99%
“…From an analytical point of view, buprofezin (as a single analyte) has been extracted with acetone from hulled rice and fruits (including apple, pear, and persimmon) and then purified using liquid–liquid partitioning and Florisil column chromatography before being analyzed using high‐pressure liquid chromatography (HPLC) coupled with an ultraviolet detector (UVD) or mass spectrometer (MS) for confirmation (Lee and Jang, ). Using multiresidue analysis, Yoon et al ., () estimated the biological half‐life and final residue levels of buprofezin and teflubenzuron in peaches over a 14‐day cultivation period using a gas chromatography–electron capture detector. In this study, the samples are extracted with acetone, partitioned with n ‐hexane, and purified using Florisil SPE.…”
Section: Introductionmentioning
confidence: 99%